2006
DOI: 10.1109/jqe.2006.881828
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Analysis of Threshold Current in Infrared Vertical-Cavity Surface-Emitting Lasers

Abstract: Abstract-The temperature dependence of threshold current th in vertical-cavity surface-emitting lasers (VCSELs) can be approximated by the equation th ( ) = + ( min ) 2 , where min is the temperature of lowest th and are parameters, and temperature is . We compare the temperature dependence of threshold current in VCSELs with GaAs, InGaAs, and strain compensated InGaAs-GaAsP quantum wells. From our analysis we find the coefficient is related to the gain properties of the quantum well, and is shown to serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 20 publications
(9 reference statements)
3
20
0
Order By: Relevance
“…4. The threshold current shows a parabolic dependence on temperature which typical for VCSELs that exhibit a gain offset design [5], [16].…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…4. The threshold current shows a parabolic dependence on temperature which typical for VCSELs that exhibit a gain offset design [5], [16].…”
Section: Resultsmentioning
confidence: 95%
“…The variation of threshold current (I th ) with temperature can be well approximated by the quadratic relationship [16] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent measurements on a probing station showed that the electrical isolation between adjacent elements was of the order of 5 MΩ, which suggests that the increase in SNR was due solely to the temperature rise in the sensing laser. The injection current for the optimum SNR also slightly increases when the neighbouring lasers are turned on, which suggests that the initial temperature of the laser array is on the hot side of the parabolic threshold current temperature profile [12,18]. Further increase in operating current of the neighbouring VCSELs leads to a monotonic increase in maximum achievable SNR.…”
Section: Achievable (Over a Range Of Operating Injection Currents)mentioning
confidence: 97%
“…Subsequent measurements on a probing station showed that the electrical isolation between adjacent elements was of the order of 5 MΩ. The injection current for the optimum SNR also slightly increases when the neighbouring lasers are turned on, which follows the increase in the threshold current with temperature as observed in a single channel system [122,207]. This suggests that the increase in SNR is due solely to the temperature rise in the sensing laser.…”
Section: Introductionmentioning
confidence: 70%